Effect of topically applied hyaluronic acid on pain and palatal epithelial wound healing: An examiner-masked, randomized, controlled clinical trial - DOĞAN, BAŞAK; ÖZTÜRK ÖZENER, HAFİZE; YILDIRIM, HATİCE SELİN (AMER ACAD PERIODONTOLOGY, 2018)
Background: This study aims to evaluate the effects of two different concentrations of topical hyaluronic acid (HA) on postoperative patient discomfort and wound healing of palatal donor sites after free gingival graft (FGG) surgery. Methods: Thirty-six patients requiring FGG were randomly assigned into three groups in an examiner-masked, randomized, controlled clinical trial. After harvesting palatal grafts, 0.2% and 0.8% HA gels were used in test groups 1 and 2, respectively. Gels were applied on donor sites and protected with periodontal dressing in the test groups, whereas the wound was covered only with periodontal dressing in the control group. On days 3, 7, 14, and 21, pain and burning sensation were recorded using a visual analog scale (VAS) as well as other parameters such as complete epithelization (CE) and color match on days 3, 7, 14, 21, and 42. Results: Test groups experienced less pain than the control group on days 3 and 7 (P < 0.001 and P < 0.001, respectively). Mean VAS score for burning sensation was higher in the control group on day 3 compared with test groups 1 and 2 (P = 0.03 and P = 0.02, respectively). CE in all patients was achieved on day 21 in both test groups, whereas it was achieved on day 42 in the control group. The test groups showed higher color match scores than the control group on days 21 (P < 0.001 and P < 0.001, respectively) and 42 (P = 0.004 and P = 0.002, respectively). Conclusion: Topical application of HA exhibits positive impact on postoperative pain and burning sensation, and accelerates palatal wound healing in terms of epithelization and color match.
Keywords: operative; pain; postoperative complications; surgical procedures; transplants; wound healing; SUBEPITHELIAL CONNECTIVE-TISSUE; SODIUM HYALURONATE; DONOR SITE; PERIODONTAL SURGERY; HEMOSTATIC AGENTS; PATIENT MORBIDITY; GRAFT; COVERAGE; EFFICACY; GEL